2016
DOI: 10.1111/jan.13069
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of spirituality on professional values and self‐efficacy: a study of senior nursing students

Abstract: Spirituality can be a foundation that provides senior nursing students with higher self-efficacy so that they are able to perform their professional roles based on their professional values. The findings can guide nursing educators to include spiritual development of nursing students to enhance the self-efficacy of senior nursing students, the future of the nursing profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
1
12
0
2
Order By: Relevance
“…created a Professional Values survey from the AACN baccalaureate essentials, components of Hall's core circle, the ANA Code of Ethics, and other publications. Yeun's Nursing Professional Values instrument (NPVs) has been validated and used in Korean studies . Various nursing codes of ethics were used to develop instruments in other countries .…”
Section: Discussionmentioning
confidence: 99%
“…created a Professional Values survey from the AACN baccalaureate essentials, components of Hall's core circle, the ANA Code of Ethics, and other publications. Yeun's Nursing Professional Values instrument (NPVs) has been validated and used in Korean studies . Various nursing codes of ethics were used to develop instruments in other countries .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found a positive relationship between spirituality and self-efficacy (Adegbola, 2011 ; Asghari et al, 2014 ; Han et al, 2014 ; Jun & Lee, 2016 ; Rakhshanderou et al, 2020 ; Wong & Longshore, 2008 ). Some approaches have shown people’s spirituality development to be about cognitive abilities, behaviors, and skills (Oman et al, 2009 ).…”
Section: Present Studymentioning
confidence: 99%
“…The more inner self-knowledge and spiritual development nurses have, the better integrated and better equipped they are to help and support those who suffer. Spirituality generates reflection in professionals, capable of stimulating feelings and behaviors of competence, confidence and understanding of their roles in a more complete way through self-awareness and the meaning of their actions (3,15) .…”
Section: Discussion Category I -Understanding the Meaning Of Spirituamentioning
confidence: 99%